Eksplorasi Ambiguitas Peran dan Stres Kerja Terhadap Kinerja Karyawan: Peran Mediasi Organizational Citizenship Behavior - Syah, Amirul; Farisi, Salman; Arif, Muhammad; Ikhsan, Ikhsan; Nasution, Azly Anggraini (JURNAL ILMIAH MANAJEMEN & BISNIS, 2024)
Purpose –  This study aims to test and analyze the effect of role ambiguity and work stress on employee performance directly and indirectly through organizational citizenship behaviour in hospitality companies in Medan.Method – This study used a quantitative approach with a survey method. Data were collected using a structured questionnaire to measure the research variables objectively. The research population is all permanent employees of the hospitality industry in Medan city, have a tenure of more than one year, and must work in an environment with a hierarchical structure that supports the measurement of role ambiguity. The study sample was taken from as many as 100-200 employees of the hospitality industry in Medan to meet one of the requirements of the data analysis method using SEM. The data analysis technique uses a quantitative approach using SEM_PLS.Findings –  The results of this study indicate that role ambiguity affects employee performance, work stress affects but is not significant to employee performance, role ambiguity, and organizational citizenship behaviour affect organizational citizenship behaviour, and there is a direct positive and significant effect between organizational citizenship behaviour on employee performance of hotel companies in Medan City. Indirectly, role ambiguity and work stress positively and significantly affect employee performance of hospitality companies in Medan.Originality/Novelty –  This study examines role ambiguity and work stress as more comprehensive predictors of employee performance and then explicitly explores the importance of organizational citizenship behaviour as a mediator in the relationship between role ambiguity and work stress and employee performance.Implications – This study has shown that organizational citizenship behaviour mediates the effect of role ambiguity and work stress on employee performance. Recommendations for further research include analyzing or using organizational citizenship behaviour variables as independent variables, not as mediating variables.